Associations of a non-synonymous variant in SLC2A9 with gouty arthritis and uric acid levels in Han Chinese subjects and Solomon Islanders. Issue 5 (31st August 2009) - Tu, Hung-Pin; Chen, Chung-Jen; Tovosia, Silent; Ko, Albert Min-Shan; Lee, Chien-Hung; Ou, Tsan-Teng; Lin, Gau-Tyan; Chang, Shun-Jen; Chiang, Shang-Lun; Chiang, Hung-Che; Chen, Ping-Ho; Wang, Shu-Jung; et al.
Abstract : Objective: To study the associations of gout, tophi and uric acid levels with the gout-related SLC2A9 (solute carrier family 2, member 9) single nucleotide polymorphisms (SNPs) between two different racial groups. Methods: Eight SLC2A9 SNPs were genotyped in 109 subjects with gout and 191 control subjects from Han Chinese men in Taiwan and 69 subjects with gout and 168 control subjects from the Solomon Islands. Results: Non-synonymous SLC2A9 rs3733591 Arg265His was associated with risk for gout and tophaceous gout in Han Chinese subjects (p=0.0012 and p=0.0044). The genetic effect of this SNP on tophaceous gout was replicated in Solomon Islanders (p=0.0184). Patients with SLC2A9 Arg265His risk C-allele consistently had a higher risk for tophi (OR 2.05–2.15) than non-tophi (OR 0.91–1.62). SNP rs3733591 described 3.68% and 5.98% of the total variability in uric acid levels for Chinese and Solomon Island subjects, respectively. Conclusion: Non-synonymous SNP rs3733591 variant within the SLC2A9 gene from two geographically diverse populations served as an important genetic checkpoint for tophaceous gout and increased uric acid levels.